2022
DOI: 10.3390/rs14205094
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monitoring of Environmental Quality in the Loess Plateau from 2000 to 2020 Using the Google Earth Engine Platform and the Remote Sensing Ecological Index

Abstract: The Loess Plateau is a typical ecologically sensitive area that can easily be perturbed by the effects of human activities and global climate change. Therefore, it is necessary to develop tools to monitor the environmental quality in the LP quickly and accurately. To reveal the spatio-temporal changes in environmental quality in the LP from 2000 to 2020, we used the Moderate-Resolution Imaging Spectroradiometer (MODIS) products on the Google Earth Engine platform and constructed the remote sensing ecological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The degraded areas are mainly located in the Inner Mongolia Autonomous Region, the Ningxia Hui Autonomous Region, and the northern and northwestern regions of Qinghai Province. For Shaanxi, Shanxi, and Henan, the degraded areas are mostly located in urban areas, such as Xi'an, Xianyang, Taiyuan, Luoyang, and other urban areas, which is consistent with previous research findings [74,75].…”
Section: Trends Of Rsei and Srsei In The Loess Plateausupporting
confidence: 91%
See 1 more Smart Citation
“…The degraded areas are mainly located in the Inner Mongolia Autonomous Region, the Ningxia Hui Autonomous Region, and the northern and northwestern regions of Qinghai Province. For Shaanxi, Shanxi, and Henan, the degraded areas are mostly located in urban areas, such as Xi'an, Xianyang, Taiyuan, Luoyang, and other urban areas, which is consistent with previous research findings [74,75].…”
Section: Trends Of Rsei and Srsei In The Loess Plateausupporting
confidence: 91%
“…In addition, there have been some improvements to the RSEI [34][35][36]. Zhang Jing, Yang Liping, and others [37] incorporated aerosol optical thickness data (AOD) into the RSEI, proposed an improved remote sensing ecological index, and used this index to evaluate the ecological environment quality of Xi'an City. The results showed that the newly constructed index considers atmospheric pollution factors and contributes to a more comprehensive evaluation of the ecological environment quality of the research area.…”
Section: Introductionmentioning
confidence: 99%
“…The RSEI values for cropland and wetland were above 0.7, with 0.724 and 0.744 respectively. Barren is the most environmentally vulnerable land use class [ 50 ], having the lowest average RSEI value of 0.53.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…After the four component indexes have been processed, the RSEI indicators are combined using the principal component analysis method. Principal component analysis, or PCA, has the advantage of automatically and impartially determining each indicator weight by examining each index's contribution to the first principle component (PC1) [31]. Equation (11) illustrates that the first output component is the initial remote sensing ecological index (RSEI PC1): RSEI0 = PC1[f(NDVI, LST,WET, NDBSI)] (11) RSEI0 must also be normalized for the computed RSEI value during the measurement procedure to enable comparability.…”
Section: Remote Sensing Ecological Index Estimationmentioning
confidence: 99%